KLASIFIKASI KEMANCETAN LALU LINTAS DI INDONESIA MENGGUNAKAN METODE NAIVE BAYES CLASSIFICATION - Ary Purwanto (Ridwan Institute, 2021)
The Puncak Jaya people are an indigenous people who still use customary law to resolve criminal cases. The use of customary law to settle criminal cases in Puncak Jaya is thought to be more successful because it can fully resolve criminal cases. Since the use of positive state legislation to resolve criminal proceedings is considered incapable of meeting the interests of both parties and may lead to tribal wars. Polri is a law enforcement agency tasked with maintaining stability and enforcing positive law in the resolution of criminal cases. The issue would then arise as the community is more likely to use common law to resolve criminal cases. This study was conducted in Puncak Jaya Regency, and it is a normative juridical study in which the data for this study was collected through a literature review. The state recognizes the existence of customary law, as specified in Article 18B paragraph (2) of the 1945 Constitution. Because of cultural customs, the Puncak Jaya community tends to resolve criminal cases using customary law. Besides, customary law is thought to be more able to accommodate the interests of those involved in criminal proceedings, owing to the presence of customary fines as punishment for customary offenses. The National Police, in carrying out its function as a law enforcement officer, must be aware of the presence of customary law as a state-recognized law and live in the Puncak Jaya culture. Finally, law enforcement's function is to ensure that all parties involved in criminal cases are satisfied.